1984
DOI: 10.1080/00103628409367572
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of nitrate and nitrite in the Kjeldahl nitrogen determination of soils and plant materials using sodium thiosulphate

Abstract: Sodium thiosulphate was used in a modification of the regular Kjeldahl method for the determination of total N in soil and plant samples containing NO�-N and NO;-N. Quantitative recoveries of added 15 N-labelled and unlabelled NO;-N (1000 �g N), NO;-N (500 �g N), and NO;-N (500 �g N) + NO;-N (Z50 �g N) were obtained from soils, plant materials and adenine, even in the presence of water (up to 50 ml H Z O/sample) when 5 g of_ Na Z S Z 0 3 .5H Z O as Z5% aqueous solution was added to each sample before digestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…The soil samples taken for analysis from 0-15 cm soil layer were analyzed in the laboratory using standard procedures. Available N, P and K were determined by the methods described by Dalal et al, (1984); Subbiah and Asija (1956); Olsen et al, (1954), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The soil samples taken for analysis from 0-15 cm soil layer were analyzed in the laboratory using standard procedures. Available N, P and K were determined by the methods described by Dalal et al, (1984); Subbiah and Asija (1956); Olsen et al, (1954), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This was done using the waterlogged procedure of Waring and Bremner (1964), and total-N (<0.25 mm size) by modified Kjeldahl method (Dalal et al . 1984).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…Another important criterion for N balance studies, is the inclusion of nitrate in the Kjeldahl N. Several methods have been proposed to include nitrate in the total N [2,4]. A critical evaluation of different methods for inclusion of nitrate and nitrite using 15N labelled compounds showed that the sodium thiosulfate method gives quantitative recovery of nitrate and nitrite [4].…”
Section: General Discussion and Review Of Literaturementioning
confidence: 99%
“…The method used for total N determination was a macro-version of the Kjeldahl method modified to include nitrate and nitrite using sodium thiosulfate [4]. In addition to effecting quantitative recovery of nitrate, this method does not require pretreatment of samples with water as is needed in case of the salicylic acid--sodium thiosulfate or KMnO4-Fe modifications of the Kjeldahl method for some soils [1,5].…”
Section: Methodsmentioning
confidence: 99%